EFFECTIVE BOND LENGTH MODEL FOR CFRP BONDED CONCRETE EXPOSED TO MARINE ENVIRONMENT - FAZLI, HAMED (2018)
Shear resistance in concrete members is an important concern due to the brittle and catastrophic nature of the shear failure. Long term degradation and deterioration, improper structural design, over flexural strengthening or increases in loads are the reasons that can arise the shear failure. Deterioration of marine concrete structures and their strengthening are challenges of the world today. Among the several shear strengthening techniques, the increasing use of carbon fibre reinforced polymer (CFRP) composite appears to be a solution for strengthening of the reinforced concrete (RC) structures. CFRP application has an exceptional physical and mechanical properties such as its high strength-to-weight ratio and easy installation of the application. Therefore, develop experimental studies on CFRP strengthening technique under the environmental condition, lead to a clear understanding of its performance in real service life.